(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The present investigation deals with simple, sensitive, rapid, precise and accurate reverse phase high performance liquid chromatography (RP-HPLC) method developed and validated for simultaneous estimation of Hydroquinone, Allantoin and Tretenoin in a cream formulation. The chromatographic separation was achieved on a reversed-phase InertsilC18 (4.6mm I.D. × 250mm, 5μm) column using a mobile phase consisting of Buffer (pH 3.5) 0.05M Potassium dihydrogen ortho phosphate-Methanol (70:30% V/V) at a flow rate of 1-mL/min and UV detection at λmax 223 nm. The method showed linearity with correlation coefficient of Hydroquinone, Allantoin and Tretenoin was 0.999, 0.999 and 0.999 over the range of 100–300 μg/mL, 50 to 150 μg/mL and 0.625 to 1.875 μg/mL, respectively. The mean recoveries were found to be 99.00 to 101.00% for all the components. The method was validated as per the ICH guidelines. The developed protocol was most accurate, repeatable, and detectable towards hydroquinone, allantoin and tretenoin in combination without any unwanted interference. When evaluated on various parameters like system suitability, precision, accuracy, linearity, robustness, stablity study, the method is efficient in separating the API from its degradants and can be utilized for analyzing the samples of hydroquinone, allantoin and tretenoin.